2022
DOI: 10.2340/actadv.v102.1105
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance Confocal Microscopy and Electrical Impedance Spectroscopy in the Early Detection of Melanoma in Changing Lesions during Long-term Follow-up of Very High-risk Patients

Abstract: Electrical impedance spectroscopy has clinical relevance in diagnosing malignancy in melanocytic lesions. Sixty-eight lesions with changes during digital follow-up of patients at very high risk of developing melanoma were prospectively included in this study from February to December 2016. Electrical impedance spectroscopy and reflectance confocal microscopy were performed to evaluate their performance in this subset of difficult lesions. Forty-six lesions were considered suspicious on reflectance confocal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The results were compared to dermoscopy in a reader study, showing the superiority of Nevisense for medium level experienced dermatologists and similar for experts. Rocha et al showed that Nevisense could reduce the need for follow-up of suspicious lesions due to its good negative predictive values [ 111 ] However, in a recent study of atypical melanocytic lesions under digital follow-up of high-risk patients for melanoma, Chavez-Bourgeois et al showed that Nevisense may have lower sensitivity in early small melanomas which were undetectable on clinical and dermoscopic examination in this group of patients [ 112 ] The conclusion of these results is that although Nevisense showed high sensitivity in early melanoma in the pivotal study, the clinical context and population of patients may impact the outcome, as with every diagnostic method. In the future, the algorithms used in nevisense will need to consider patient’s risk factors and clinical situations ( Figure 13 ).…”
Section: Techniquesmentioning
confidence: 99%
“…The results were compared to dermoscopy in a reader study, showing the superiority of Nevisense for medium level experienced dermatologists and similar for experts. Rocha et al showed that Nevisense could reduce the need for follow-up of suspicious lesions due to its good negative predictive values [ 111 ] However, in a recent study of atypical melanocytic lesions under digital follow-up of high-risk patients for melanoma, Chavez-Bourgeois et al showed that Nevisense may have lower sensitivity in early small melanomas which were undetectable on clinical and dermoscopic examination in this group of patients [ 112 ] The conclusion of these results is that although Nevisense showed high sensitivity in early melanoma in the pivotal study, the clinical context and population of patients may impact the outcome, as with every diagnostic method. In the future, the algorithms used in nevisense will need to consider patient’s risk factors and clinical situations ( Figure 13 ).…”
Section: Techniquesmentioning
confidence: 99%